Psychotic experiences and religiosity: data from the WHO World Mental Health Surveys. (16th February 2018) - Kovess‐Masfety, V.; Saha, S.; Lim, C. C. W.; Aguilar‐Gaxiola, S.; Al‐Hamzawi, A.; Alonso, J.; Borges, G.; de Girolamo, G.; de Jonge, P.; Demyttenaere, K.; Florescu, S.; Haro, J. M.; et al.
Abstract : Objectives: Religiosity is often associated with better health outcomes. The aim of the study was to examine associations between psychotic experiences (PEs) and religiosity in a large, cross‐national sample. Methods: A total of 25 542 adult respondents across 18 countries from the WHO World Mental Health Surveys were assessed for PEs, religious affiliation and indices of religiosity, DSM‐IV mental disorders and general medical conditions. Logistic regression models were used to estimate the association between PEs and religiosity with various adjustments. Results: Of 25 542 included respondents, 85.6% (SE = 0.3) ( n = 21 860) respondents reported having a religious affiliation. Overall, there was no association between religious affiliation status and PEs. Within the subgroup having a religious affiliation, four of five indices of religiosity were significantly associated with increased odds of PEs (odds ratios ranged from 1.3 to 1.9). The findings persisted after adjustments for mental disorders and/or general medical conditions, as well as religious denomination type. There was a significant association between increased religiosity and reporting more types of PEs. Conclusions: Among individuals with religious affiliations, those who reported more religiosity on four of five indices had increased odds of PEs. Focussed and more qualitative research will be required to unravel the interrelationship between religiosity and PEs.